(untitled) (Research, Society and Development, 2023)
Objective: The objective of this study was to identify the endophytic fungal genera associated with Hamelia patens seeds and to verify the antimicrobial potential of the extracts of the selected isolates. Method: For this, the classes of compounds produced by thin layer chromatography (TLC) were suggested, and the biological activity of fungal extracts against strains of phytopathogenic fungi, yeast, gram-negative and gram-positive bacteria was evaluated. Results: 8 fungal genera associated with the seeds were identified as endophytes. The genus with the highest incidence was Diaporthe with 60%. There was inhibition of phytopathogens in all in vitro tests, except for the volatile metabolites test against Fusarium oxysporum. In the antibiogram evaluation, the isolates HP3, HP5 and HP6 stood out in the inhibition of Pseudomonas aeruginosa, Staphylococcus aureus and Streptococcus pyogenes. From CCD assay (Thin Layer Chromatography) bioactive compounds such as terpenoids, phenolic compounds and coumarins were evidenced both in the mycelium and in the fermented broth of the fungal isolates. Discussion: Inhibition of the pathogens was verified in all the assays against phytopathogens, except for F. oxysporum in the volatile metabolites test. In the antibiogram, inhibition of P. aeruginosa, S. aureus and S. pyogenes bacteria was verified. Among the classes of compounds suggested by CCD in the fermented broth and mycelium are terpenoids, coumarins and phenolic compounds. Conclusion: The data obtained in this study bring unprecedented information regarding the fungal diversity associated with seeds as endophytes, being the first report of the association of endophytic fungi in H. patens seeds.